(untitled) (Jurnal Pustaka, 2025)
This study aims to (1) describe the types of assessments used in the implementation of the Merdeka Curriculum for Japanese language learning at SMAN 4 Singaraja, and (2) identify the challenges encountered in the implementation of these assessments. This research employed a descriptive qualitative method, with data collected through observation and interviews. The subject of the study was the Japanese language teacher. The results indicate that (1) Japanese language instruction at SMAN 4 Singaraja utilizes three types of assessments: diagnostic, formative, and summative. Diagnostic assessment is conducted at the beginning of instruction to determine students’ readiness, followed by formative assessment throughout the learning process, and concluded with summative assessment to measure students’ learning outcomes. All three types of assessments are implemented based on the principles of the Merdeka Curriculum. (2) The challenges identified in the implementation of assessment include the diverse characteristics of students, limited instructional time, and insufficient teaching materials or textbooks.